2022
DOI: 10.1177/15579883221120985
|View full text |Cite
|
Sign up to set email alerts
|

Health and Social Inclusion: The Impact of Psychological Well-Being and Suicide Attempts Among Older Men Who Have Sex With Men

Abstract: Older adults’ mental health and suicidal tendencies have garnered much attention because of their vulnerability. Few studies have examined the impact of psychological well-being and suicide attempts among older men who have sex with men (OMSM). This study examines the levels of depression and suicidal tendencies among OMSM, factors impacting their mental health, and their likelihood of committing suicide. Descriptive statistics are used to analyze the correlation between depression and suicidal tendencies amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 43 publications
0
19
0
1
Order By: Relevance
“…Among those who have committed suicide, 50–70% have suffered from depression ( 4 ). Depression and suicide in older adults have garnered much attention because of their vulnerability ( 5 ). China has entered an aging society, with the proportion of the elderly in the total population rising to 18.7% ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among those who have committed suicide, 50–70% have suffered from depression ( 4 ). Depression and suicide in older adults have garnered much attention because of their vulnerability ( 5 ). China has entered an aging society, with the proportion of the elderly in the total population rising to 18.7% ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…This item is often used in research studies to evaluate suicidal behavior. Previous studies have also reported that high levels of suicidal ideation, indicated by the ninth item of PHQ-9, is a robust predictor of suicide attempts and deaths [ 22 , 23 , 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ristevska-Dimitrovska and Batic ( 37 ) discovered that sufferers with improved psychological wellbeing also improved their quality of life, while their functioning improved. While successfully relieved cancer-related symptoms, Ristevska-Dimitrovska and Batic ( 37 ) also noted that adaptability was a potential mechanism against depression and psychological illnesses ( 38 ). Carver stresses that early sufferers who have a high level of hopeful may not only have more realistic predictions about their state, but also have a more favorable impact on postoperative recovery ( 39 , 40 ).…”
Section: Literature Reviewmentioning
confidence: 99%